Aportació al coneixement dels macromicets de l’illa de Mallorca II - Pérez-De-Gregorio i Capella, Miquel Àngel (Revista Catalana de Micologia, 2007)
A contribution to the knowledge of the macromycetes of Majorca Island. II. (Balearic Islands). This work reports 40 species: 3 Ascomycetes and 37 Basidiomycetes. After our information, 37 of them are new records for the Balearic Islands, and a further 3 are new records for Majorca. Of special interest are: Suillus bellinii f. lutea forma nova, Boletus dryophilus, Greletia ovalispora, Peziza saccardiana, Trametes hirsuta, Clitocybe cistophila, Cortinarius sodagnitus, Cortinarius subfulgens, Hebeloma pyrophilum, Hygrophorus quercetorum, Marasmius carphaticus, Mycena polyadelpha and Hydnangium aurantiacum.